2017
DOI: 10.1002/ar.23737
|View full text |Cite
|
Sign up to set email alerts
|

Internal Ophthalmic Arteries Within the Brain‐Base Arterial System in Guinea Pig

Abstract: In situ vascular specimens of the arterial circle were collected from 15 adult guinea pigs, both male and female. After specimen preparation, the vessels were filled with synthetic latex and subjected to analysis. Similar as in the case of other rodents, vertebral arteries were merged into basilar artery, further dividing into two short terminal branches. Distally, the terminal branches extend into caudal cerebral arteries. Rostral part of the arterial circle of brain is supplied with blood from maxillary arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…A partial explanation may lie in the arterial system. Multiple animal studies investigating vasculature found interophthalmic arteries present in rabbits and guinea pigs, providing a possible route for the transfer of drugs as well as materials produced in response to trauma (Forster et al, 1979 ; Kuchinka, 2017 ). While the mechanisms underlying these interocular effects are not fully understood, it is interesting that we only observed contralateral damage in the SNP animals.…”
Section: Discussionmentioning
confidence: 99%
“…A partial explanation may lie in the arterial system. Multiple animal studies investigating vasculature found interophthalmic arteries present in rabbits and guinea pigs, providing a possible route for the transfer of drugs as well as materials produced in response to trauma (Forster et al, 1979 ; Kuchinka, 2017 ). While the mechanisms underlying these interocular effects are not fully understood, it is interesting that we only observed contralateral damage in the SNP animals.…”
Section: Discussionmentioning
confidence: 99%
“…However, in camels, it resembles the number "8" (Kiełtyka-Kurc et al, 2014), as in the American tapir (Frąckowiak & Giejdasz, 1998), while in equines, it takes the shape of a rectangle (Frąckowiak & Giejdasz, 1998). In rodents, the shape of the arterial circle of the brain resembles an ellipse (Aydin, 2008;Aydin et al, 2005Aydin et al, , 2009Azambuja et al, 2018;Brudnicki et al, 2014;Kuchinka, 2017aKuchinka, , 2017bSilva et al, 2016). In animals from the order of lagomorphs (Lagomorpha), the shape of the arterial circle of the brain is very specific, similar to that of an hourglass (Brudnicki et al, 2012(Brudnicki et al, , 2015.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the final division of the internal carotid artery are two branches: the rostral cerebral artery, and the internal ophthalmic artery. In some rodent species, the internal ophthalmic artery has been found to have a large diameter [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study that was conducted by König [ 41 ] on domestic cattle, the arterial circle of the brain was open on the rostral side in the majority of the cases. An open arterial circle of the brain was also found in representatives of rodents, such as in the guinea pig [ 36 , 42 ], nutria [ 43 ], the ground squirrel [ 44 ], and the chinchilla [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation